1997
DOI: 10.1902/jop.1997.68.9.842
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Smoking on Serum IgG2 Reactive With Actinobacillus actinomycetemcomitans in Early‐Onset Periodontitis Patients

Abstract: High titers of serum IgG2 reactive with Actinobacillus actinomycetemcomitans are present in early‐onset periodontitis (EOP) patients and it appears that anti‐A. actinomycetemcomitans may be protective. Smoking is associated with increased periodontal disease severity in generalized early‐onset periodontitis (G‐EOP) patients, but is not associated with periodontal disease severity in patients with localized juvenile periodontitis (LJP). Furthermore, smoking is associated with reduced serum IgG2 levels in black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
1
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 34 publications
4
66
1
5
Order By: Relevance
“…We conclude that gingival fibroblast cell populations derived from different normal subjects react differently to these bacterial challenges and suggest the potential for host variability in responsiveness. Currently, few genetic studies on periodontitis have been performed, although promising evidence suggests some genetic linkage (15,24,47), including host response alterations associated with genetic polymorphisms (19,31,45). These published studies suggested a genetic contribution to the characteristics of the inflammatory and immune response to oral bacterial challenge and the subsequent expression of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…We conclude that gingival fibroblast cell populations derived from different normal subjects react differently to these bacterial challenges and suggest the potential for host variability in responsiveness. Currently, few genetic studies on periodontitis have been performed, although promising evidence suggests some genetic linkage (15,24,47), including host response alterations associated with genetic polymorphisms (19,31,45). These published studies suggested a genetic contribution to the characteristics of the inflammatory and immune response to oral bacterial challenge and the subsequent expression of periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been associated with decreased levels of serum IgG antibodies to oral bacteria (60) and decreased serum concentrations of the water-soluble antioxidant ascorbate (58). Smoking also was a significant contributor to our bivariate models of serum IgG antibody levels (Table 1).…”
Section: Serum 8-isoprostane Related To Serum Igg Antibody Levelsmentioning
confidence: 91%
“…Clinical conditions associated with increased oxidative stress in humans [e.g., smoking (56), diabetes (23), periodontitis (12), and aging (42)] have been associated with impaired immune function (44). Smoking, a recognized risk factor for periodontitis (7), has been associated with depressed levels of total serum IgG2 (55), which is a Th1-dependent IgG antibody subtype, and with decreased serum levels of antibody for selected oral bacteria (60). Diabetes has been associated with changes in T-cell populations and decreased IgG antibody responses to oral bacteria (20).…”
mentioning
confidence: 99%
“…Son zamanlarda yapılan deneysel ve klinik çalışmalar, sigaranın periodontal hastalık üzerine olan immun enflamatuvar etkisine odaklanmıştır. Damarlarda vazokonstrüksi-yon, kan akımında azalma, osteoklast aktivitesinde artış, kollajen sentezinde azalma ve kollajenaz üretiminde artışa neden olarak lokal [25][26][27] yollarla, PMNL'lerin fagositoz ve kemotaksis fonksiyonlarında bozulma, proenflamatuvar sitokinlerin salınımında artış ve periodontopatojenlere karşı antikor üretimini azalmaya neden olarak sistemik 27,28 yollarla periodontal hastalık patogenezinde ve gelişiminde rol oynamaktadır. Sigara içen bireylerin içmeyenlere göre periodontal hastalığa yakalanma olasılığının 3-6 kez daha fazla olduğu rapor edilmiştir.…”
Section: Grupların Oluşturulmasıunclassified